The Disciplinary Direction and Structure of Journalism and Media Education - Lee, Jae-won; Kim, Won-yong (Bodhi: An Interdisciplinary Journal, 2010)
Reviewing the communication industry, the cybernetics pioneer Norbert Wiener (1950) once offered a very disturbing observation: "The people who have elected communication as a career so often have nothing more to communicate." It's more than half a century from the days of his comment on us, but are we in any better shape now? DOI: 10.3126/bodhi.v2i1.2861 Bodhi Vol.2(1) 2008 p.1-13